ANALISIS GAYA BELAJAR MAHASISWA SEMESTER AWAL PADA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS PAMULANG - Nurhasanah, Enok; Tasia, Fanni Erda; Hamda, Nasmal (Pamulang university, 2024)
This research aims to analyze the learning styles of students in the first semester, namely semester 1, at the Pamulang University Economic Education Study Program using a quantitative approach and phenomenological methodology. The research subjects were 6 students in the first semester of the Economic Education Study Program as Key Informants and 2 lecturers who taught in the first semester as informants. The data collection technique used was interviews. The data analysis technique for this research is by means of data collection, data reduction, data display, and conclusion drawing/verification. The results of the research show that early semester students have a tendency towards a visual learning style where students prefer to learn by clearly seeing what the lecturer says, starting from mouth movements, hand movements and writing made by the lecturer on the blackboard. Students also tend to write down points that they consider important during the lecture process. This is in line with one of the characteristics of the visual learning style, which is that they enjoy writing down the information they get. By being aware of their respective learning styles and carrying out learning activities according to their learning styles, students can understand the material being studied more optimally. Thus, it can be concluded that students in the first semester of the Economic Education Study Program for the 2023/2024 Odd Semester Academic Year tend to have a visual learning style.Keyword: Education; Study; Learning Style.